EFFECT OF ENTREPRENEURSHIP EDUCATION AND ENTREPRENEURIAL ORIENTATION ON BUSINESS PERFORMANCE THROUGH ENTREPRENEURIAL ATTITUDE - Anfi, Dieva Zahrohtu; Pratesa, Dimas putri Mega; Rahma , Adelia; Zulfikar, Muhammad Vicky (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Business performance is an effort made to maximize company profits obtained from providing value to customers by innovating to serve customer needs. Involving customers in an innovation process can be a mutually beneficial symbiotic relationship. This study examines the direct and indirect effects of Entrepreneurship Education, Entrepreneurial Orientation, and Entrepreneurial Attitude on business performance. The sample in this study was 250 entrepreneurial students in Malang. The data analysis techniques used were descriptive statistical analysis, multiple linear regression analysis, and path analysis. This study found that there is a direct influence of entrepreneurship education and entrepreneurial orientation on entrepreneurial attitude. Entrepreneurship education, entrepreneurial orientation, entrepreneurial attitude towards business performance. An indirect influence of entrepreneurship education on business performance through entrepreneurial attitude. There is an indirect influence of entrepreneurial orientation on business performance through entrepreneurial attitude